2010
DOI: 10.15218/zjms.2010.011
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of mandibular third molar impaction in patients attended the Hawler College of Dentistry: a retrospective radiographic study

Abstract: Background and objective: The aim of this study was to assess radiographically the angulations and depth of impacted mandibular third molars. Methods: In a retrospective study 163 impacted mandibular third molars of 100 patients were examined on orthopantomograms (OPT) in the College of Dentistry/ Hawler Medical University during 2008. From these orthopantomograms the angulations (mesioangular, distoangular, vertical, and horizontal) and the depth (types A, B, and C) of the impacted mandibular third molars we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
2
0
0
Order By: Relevance
“…There was a statistically significant association between 25 and 34 years' age group and orofacial pain, which is in agreement with Pau et al 26 and Kurchid et al 27 Pain originated from dentoalveolar and supporting structures contributed to the highest numbers of patients with age group of 25 to 34 years old compared with other types of orofacial pain. Among this type of orofacial pain, pulpitis and pericoronitis are the commonest form of dental condition in this age group that cause patients to seek for a treatment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There was a statistically significant association between 25 and 34 years' age group and orofacial pain, which is in agreement with Pau et al 26 and Kurchid et al 27 Pain originated from dentoalveolar and supporting structures contributed to the highest numbers of patients with age group of 25 to 34 years old compared with other types of orofacial pain. Among this type of orofacial pain, pulpitis and pericoronitis are the commonest form of dental condition in this age group that cause patients to seek for a treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Those findings are in contrast to study done by Smiljic et al 21 and Aggarwal et al 22 However, the present study showed that there was statistically no significant difference between genders in relation to orofacial pain, which is in line with Rikmasari et al 23 In addition, the number of females was more than males in pericoronitis which is similar to the studies performed by Yamalik and Bozkaya 24 and LeResche. 25 There was a statistically significant association between 25 and 34 years' age group and orofacial pain, which is in agreement with Pau et al 26 and Kurchid et al 27 Pain originated from dentoalveolar and supporting structures contributed to the highest numbers of patients with age group of 25 to 34 years old compared with other types of orofacial pain. Among this type of orofacial pain, pulpitis and pericoronitis are the commonest form of dental condition in this age group that cause patients to seek for a treatment.…”
Section: Discussionsupporting
confidence: 82%